Real Exchange Rate Behavior: The Recent Float from the Perspective of the Past Two Centuries - Lothian, James R.; Taylor, Mark P. (Journal of Political Economy, 1996)
Using annual data spanning two centuries for dollar-sterling and franc-sterling real exchange rates, the authors find strong evidence of mean-reverting real exchange rate behavior. Using simple, stationary, autoregressive models estimated on prefloat data, they easily outperform nonstationary real exchange rate models in dynamic forecasting exercises over the recent float. Such stationary univariate equations explain 60-80 percent of the in-sample variation in real exchange rates, although the degree of short-run persistence may be high. The econometric estimates imply a half-life of shocks to the real exchange rate of about six years for dollar-sterling and a little under three years for franc-sterling. Copyright 1996 by University of Chicago Press.